CYBERSECURITY AND THREATS TO THE AVIATION SECTOR: LEGAL ASPECT - Filinovych, Valeria (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Today information technologies are used everywhere – in all spheres of social interaction, including and in aviation. This use of the benefits mentioned is not without several problems, especially concerning security. Cyber threats are usually transnational and have a corresponding impact at both the national, territorial, and international levels. Civil aviation today cannot exist outside of cybersecurity. Otherwise, the use of modern technologies and developments in the transport field will not make sense, especially in connection with the growing problem of cyber terrorism. Purpose: to study the features and current state of cybersecurity in the aviation sector and the legal possibilities for its protection. Research methods that were used during the research are generally recognized methods of scientific knowledge, namely: analytical, comparative-legal, systemic and structural, and others. The results: the concept, essence, characteristics, and features of cybersecurity in the aviation sector were studied, the problems of protecting critical infrastructure facilities, air carriers, and passengers were pointed out, and suggestions for overcoming such problems were presented. Discussion: the discussion in the study is devoted to finding ways for solving the problem of ensuring a reliable level of cybersecurity in aviation computer systems and networks and the need to harmonize domestic legislation on this issue with international standards. Analysis of recent studies and publications made it possible to point to individual scientific and theoretical works of such scientists as R. Atkinson, P. Bilenchuk, T. Kisling, S. Lykhova, I. Polishchuk, I. Sopilko, E. Ukvandu, N. Filyk, H. Hindi, Y. Tsigler and others. Most countries in the world are concerned about maintaining an adequate level of cybersecurity in the aviation sector. Therefore, they are actively introducing new methods to identify possible cyber threats. However, knowing about the existing threat is only part of the matter; we cannot do without developing appropriate methods of protection. There is a set of technical means of protection used in this area, but they do not give a 100% guarantee. Concerning legal protection, it is necessary to develop new and improve the existing regulatory legal acts to ensure timely warning, detection, and response to cyber-attacks. To develop an effective cybersecurity framework in the aviation sector, it is necessary, inter alia, to harmonize national legislation with international standards; ensure timely and adequate response to cyber incidents; establish and apply common cyber standards and aviation systems regulations to mitigate risks; actively use the methods recommended by ICAO to ensure flight safety and not only. In the opinion of the author of the study, trying to solve the problem under consideration using only one sectoral method will not lead to success, which is why it is important to use a mixture of technical and legal, and socioeconomic means.